OBSTACLES FACING THE TRAINING PROFESSION IN ARTISTIC GYMNASTICS FROM THE POINT OF VIEW OF COACHES - Oras Qassim Mohammed; Found Hammed Asal (Proximus Journal Publishing, 2025)
This study aims to identify the most significant obstacles facing the artistic gymnastics training profession from the perspective of coaches in Al-Anbar Governorate. Utilizing a descriptive survey methodology, the research was conducted on a purposive sample of (30) coaches during the 2025/2026 season. A questionnaire was employed to assess four primary axes: administrative and organizational obstacles, resources and equipment, coach-related factors, and obstacles regarding players and the social environment. The statistical analysis revealed significant constraints across all axes, most notably poor administrative planning, scarcity of modern equipment and training halls, and a lack of specialized development courses for coaches. Furthermore, the study identified that academic pressures on players and insufficient financial incentives significantly hinder the training process. The research concludes that these administrative and technical barriers impede athletic development and recommends the necessity of organizing scientific qualification courses for coaches, improving infrastructure, and enhancing administrative support to elevate the standard of artistic gymnastics.
Keywords: Artistic Gymnastics; Training Obstacles; Sports Coaching